Nilai Edukasi Pada Ritual Bereqe Lombok (Kajian Etnografi) - Lalu Nasrulloh (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2020)
Background of the problems involved in this study is based on what researchers have found to be indigenous and culture abuators on the island of Lombok. More and more, local cultures are strictly ritualized without any deep significance about its value. So many local cultures should have been preserved by cultural agents, but they are being pushed asided even more. They regarded the local culture as out of date, ashamed of its own culture as a slogan for generations of the nation’s successor. Like the bereqe Sasak Lombok ritual, which is a typical sasak culture, there is no known presence in the sasak community. So this is the reason for revealing the educational value found in the bereqe riyual. Cultural values could provide as shield to maintain local cultural values without being displaced even with extinction. The purpose of this research is (1) to identify the educational value forms in the Lombok bereqe ritual (2) to uncover and preserved the local Lombok culture. The method used in data collection is the method of documenting, see, hear, and log it.